Linguistic sexism and gender role stereotyping in Malaysian English Language textbooks - Bahiyah Dato’ Hj. Abdul Hamid; Mohd. Subakir Mohd. Yasin; Kesumawati Abu Bakar; Yuen, Chee Keong; Azhar Jalaluddin (Penerbit UKM, 2008)
Sexist language and gender stereotyping do not only disparage, but can also lower the dignity of one group of people, usually women/girls. If left unchecked, these negative norms of behavior and attitude could be institutionalized and gradually become part of our social and cultural code. Recent research findings indicate a strong presence of gender bias and linguistic sexism in the language and content of educational materials such as textbooks and practice books. This paper addresses linguistic sexism and gender role stereotyping in Malaysian English language school textbooks. Specifically, it looks at: If sexism is inculcated very early in life, how is it inculcated and what is inculcated? Are our school textbooks indirectly and unconsciously functioning as a conduit for the indoctrination and enforcement of sexism and sex role conformity among young Malaysians? This paper presents the preliminary findings of an on-going research study that documents the extent of gender bias and linguistic sexism in selected Malaysian primary and secondary school English language textbooks.